Cleavage furrow organization requires PIP(2)-mediated recruitment of anillin. - Liu, J.; Fairn, G.D.; Ceccarelli, D.F.; Sicheri, F.; Wilde, A. (Current Biology, 2012)
Cell division is achieved by a plasma membrane furrow that must ingress between the segregating chromosomes during anaphase [1-3]. The force that drives furrow ingression is generated by the actomyosin cytoskeleton, which is linked to the membrane by an as yet undefined molecular mechanism. A key component of the membrane furrow is anillin. Upon targeting to the furrow through its pleckstrin homology (PH) domain, anillin acts as a scaffold linking the actomyosin and septin cytoskeletons to maintain furrow stability (reviewed in [4, 5]). We report that the PH domain of anillin interacts with phosphatidylinositol phosphate lipids (PIPs), including PI(4,5)P(2), which is enriched in the furrow. Reduction of cellular PI(4,5)P(2) or mutations in the PH domain of anillin that specifically disrupt the interaction with PI(4,5)P(2), interfere with the localization of anillin to the furrow. Reduced expression of anillin disrupts symmetric furrow ingression that can be restored by targeting ectopically expressed anillin to the furrow using an alternate PI(4,5)P(2) binding module, a condition where the septin cytoskeleton is not recruited to the plasma membrane. These data demonstrate that the anillin PH domain has two functions: targeting anillin to the furrow by binding to PI(4,5)P(2) to maintain furrow organization and recruiting septins to the furrow.